Implementation of ATIKA (Ati, Telur dan Ikan) consumption education on increasing hemoglobin levels in pregnant women - Retnaningtyas, Erma; Istiningrum, Ajeng (Institute Of Computer Science (IOCS), 2024)
Consuming animal protein, especially ATIKA (Ati, Telur dan Ikan) is an effort to increase hemoglobin levels in pregnant women. This study analyzes the implementation of ATIKA (Ati, Telur dan Ikan) observations on increasing HB levels in pregnant women at the UPTD of the Sidomulyo Health Center. Experimental research design with a pre-experimental study, one group pre-test, post-test. Population of 20 pregnant women with total sampling technique. Data collection by observation. The results of the study showed that the average hemoglobin level before consuming ATIKA was 9.6 gr/dl, while after consuming ATIKA for 3 weeks the average Hb was 10.6 gr/dl. The analysis test uses the Wilcoxson sing test with a significance of 0.001 < ? = 0.05. There is an effect of implementing Atika consumption on increasing the Hb levels of pregnant women. Regular consumption of Atika in pregnant women can increase Hb and prevent pregnancy anemia.